2009
DOI: 10.1099/vir.0.010983-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of infectious hepatitis C virus with adaptive mutations in cultured hepatoma cells

Abstract: Robust production of infectious hepatitis C virus (HCV) in cell culture was realized by using the JFH1 strain and the homologous chimeric J6/JFH1 strain in Huh-7.5 cells, a highly HCVpermissive subclone of Huh-7 cells. In this study, we aimed to establish a more efficient HCVproduction system and to gain some insight into the adaptation mechanisms of efficient HCV production. By serial passaging of J6/JFH1-infected Huh-7.5 cells, we obtained culture-adapted J6/JFH1 variants, designated P-27, P-38 and P-47. Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 55 publications
0
54
0
Order By: Relevance
“…We prepared the virus stock used in this study as described previously (Deng et al, 2008). A cell culture-adapted P-47 strain (Bungyoku et al, 2009;Deng et al, 2008) was used throughout the experiments. Virus infection was performed at an m.o.i.…”
Section: Methodsmentioning
confidence: 99%
“…We prepared the virus stock used in this study as described previously (Deng et al, 2008). A cell culture-adapted P-47 strain (Bungyoku et al, 2009;Deng et al, 2008) was used throughout the experiments. Virus infection was performed at an m.o.i.…”
Section: Methodsmentioning
confidence: 99%
“…However, genetic incompatibility between JFH1 and the alternative HCV gen ome segment fused to it often limits production of infectious virus This restriction can be overcome by serial passage of the chimeras in cell culture which over time results in the accumulation of adaptive changes compensating the genetic differences between the fused genomes and thus increases virus yields (Abe, Ikeda et al 2007;Gottwein, Scheel et al 2007;McMullan, Grakoui et al 2007;Yi, Ma et al 2007;Jensen, Gottwein et al 2008;Scheel, Gottwein et al 2008;Bungyoku, Shoji et al 2009;Gottwein, Scheel et al 2009;Gottwein, Jensen et al 2011;Koutsoudakis, Perez-del-Pulgar et al 2011;Chan, Cheng et al 2012). For instance, Yi and colleagues demonstrated that mutations in E1, p7, NS2 and NS3 contribute to the ability of a H77/JFH1 chimeric genome to assemble and release high amounts of virus particles .…”
Section: Adaptation Of Infectious Hcv Genomes To Cell Culturementioning
confidence: 99%
“…The full-length genome of isolate JFH-1 was demonstrated to be competent for viral particle production in tissue culture (22,41,46) by using Huh-7-derived cell lines that are permissive to HCV infection and replication (2,20). Several of these HCV cell culture (HCVcc) systems have been described, the most robust of which are based on chimeric J6/JFH-1 viruses or tissue culture-adapted strains of JFH-1 (1,3,4,17,18,26,36,47). However, the quantity of infectious virions these systems can produce is limited, presumably due to currently unidentified constraints on infectious virus particle production in tissue culture (5,16,26,47).…”
mentioning
confidence: 99%